Dewatering the Blast Area -- A Means of Achieving Productivity - S R. "Bob" Pilshaw (International Society of Explosives Engineers, 1988)
Productivity is the popular "buzz" word that catches the attention of most managers when it is featured in the more popular mining and construction magazines. Engineering Task Forces and teams are formed to take advantage of productivity opportunities in almost all phases of an operation except the drilling and blasting area.